The effects of the Great Migration on urban renewal - Ying Shi; Daniel Hartley; Bhaskar Mazumder; Aastha Rajan (Federal Reserve Bank of Chicago, 2021)
The Great Migration significantly increased the number of African Americans moving to northern and western cities beginning in the first half of the twentieth century. We show that their arrival shaped slum clearance and urban redevelopment efforts in receiving cities. To estimate the effect of migrants, we instrument for Black population changes using a shift-share instrument that interacts historical migration patterns with local economic shocks that predict Black out-migration from the South. We find that local governments responded by undertaking more urban renewal projects that aimed to redevelop and rehabilitate "blighted" areas. More Black migrants also led to an increase in the estimated number of displaced families. This underscores the contribution of spatial policies such as urban renewal towards understanding the long-term consequences of the Great Migration on central cities and Black neighborhoods and individuals.
Keywords: 330